3. Text-Based Conferencing Products - Garber, Debbie; Stein, Jennifer; Baggaley, Jon (International Review of Research in Open and Distributed Learning, 2002)
The basic form of online conferencing is asynchronous and text-based, and a vast array of products is now available for fully featured communication within this framework. The following set of seven reviews contrasts some of the best text-based products that have so far come to our attention, with other products whose features are less extensive. This comparison of products provides a useful look at the options now available to the designers of online conferences, and at the choices to be made in product selection. The reviews (by the first two authors, both DE graduate students) have stressed the utility of the products from the joint perspective of students and teachers.